(untitled) (Nóema, 2021)
Through the doubts Tschirnhaus poses to Spinoza about the imperceptibility of the attributes and the distiction of the divine intellect’s essence and the human intellect’s essence , this essays proposes a study of the relationship between the totality and its parts and the sense of immanence in Spinoza’s ontology, with a keen eye on the implication-explication dyad which allows it to funcyion. The formal communion proper to immanence, which grounds implication and explication, turns out to be the key concept to understand both the symphonic nature of the universe, in which each one thing recalls all other and the whole, and the delicate empiricism that defines the third kind of knowledge.